The dueling Duchess - Spencer, Minerva (Spencer, Minerva. Wicked women of Whitechapel., 2023)
"When Cecile Tremblay lost everyone and everything in the French Revolution, she never imagined that she'd earn her living as a markswoman in a London circus. But Farnham's Fantastical Female Fayre has become her home, her family, and her future. Another thing Cecile never imagined was becoming entangled with the man gossip columns call The Darling of the Ton. But mere weeks after her rejection of his insulting carte blanche--and his infuriating engagement to an heiress--Darlington is back, this time to beg Cecile for help. And help him she will, by teaching him about honest work--and the right way to treat a woman. Gaius Darlington has always led a charmed life. Until now. Suddenly, a long-lost heir has appeared to claim his title, possessions, and property. Not only that, but Guy's fiancée has jilted him to marry the usurper! Yet there is a silver lining: it's no longer Guy's duty to marry an heiress to save the dukedom. He's free to wed the woman he loves--if only he can earn her forgiveness. They say hell hath no fury like a woman scorned. But fury is just a step away from passion, and Guy knows just how to arouse Cecile's..." -- Provided by publisher.